Health services related factors affecting the pap smear services in Fiji: a qualitative study - Aliti Kunatoga; Masoud Mohammadnezhad (BMC, 2021)
Abstract Background Cervical cancer is the thirdly vast usual cause of cancer in women, and the second vast majority cause of death among women aged 14 to 44 years, both in developed and developing countries. This paper aims to explore the perception of women and Health Care Workers (HCWs) about health care related factors affecting the Pap smear services among women who are screened in the Women Wellness Centre (WWC) in Suva, Fiji. Methods This study used a qualitative method in July-September 2019 in which women screened for cervical cancer used in-depth interviews whereas HCWs used Focus Group Discussion (FGD) in WWC in Suva, Fiji. This study used purposive maximum variation sampling where participants are selected according to the inclusion and exclusion criteria. Semi-structured open ended questionnaires were used to collect the data among participants. Data coding was done until theoretical saturation was reached. Thematic analysis was used and all the text has been coded, themes were abstracted from the coded text segments. Results A total of 20 women screened for cervical cancer and 5 HCWs were present during the duration of the study. Health care system was a factor recognized by both groups to have been a cause for the hindrance of cervical screening. There were 8 themes identified from the study, 3 themes from the women screened for cervical cancer and 5 from HCWs. Nearly all the participants reported about the compromised of cervical cancer screening services delivery because of factors such as lack of equipment and supplies, shortage of staff, long distances to health facilities, turnaround time and delay of results which affect the uptake of cervical cancer screening services. Conclusion While improvement has been made in the distribution of cervical cancer screening in WWC, a number of barriers and factors affect service uptake and delivery. Investments to be made in order to address the identified barriers such as turnaround time, long distances to health facilities, shortage of supplies and staff in order to improve uptake of cervical cancer screening services.